Analisis Kegagalan pada Bearing Block Clinker Cooler PT Semen Baturaja Pabrik 2 menggunakan Failure Mode and Effect Analysis Method (FMEA) - Bagus Prasetiyo, Angger; Utomo, Putro; Sinar Saputro, Aldi (Universitas Nusantara PGRI Kediri, 2023)
The process of making cement goes through numerous phases and different procedures in order to produce cement that is up to factory requirements. In addition to the combustion process, the cooling process also exists in the cement manufacturing kiln area, particularly the rotary kiln, but it is less crucial. A crucial aspect of the cement production machinery is the cooling procedure or clinker cooler. The cooling process here impacts the quality of the cement produced, therefore this equipment is used to cool or lower the temperature of the clinker so it doesn't burn in the rotary kiln. The relationship between the clinker's crystal concentration and the liquid phase is influenced by the rate at which the clinker cools